Kartini Abad 21: Analisis Pemikiran Maudy Ayunda dalam Mendorong Reformasi Pendidikan Indonesia - Keke Ayuning Tiyas Santoso; Masduki Asbari; Devona Bunga Madania (AGUSPATI RESEARCH INSTITUTA, 2025)
This study is to explore how contemporary women, as representations of modern-day Kartini, are capable of challenging the status quo through their ideas and concrete actions, particularly in the field of education. This research employs a descriptive qualitative method using the listen-and-note technique, as data were obtained by observing verbal narratives from the YouTube channel of Gita Wirjawan, titled